(untitled) (Research in Agriculture Livestock and Fisheries, 2019)
This study was taken to determine morphometric, meristic and hematological parameters of the B. grypus (H, 1843) in Sulaimani natural water resources of Sulaimani city, Iraq. 30 fish were used in this study and allocated to three groups that depend on fish length. Total lengths were 26.71 ± 0.85, 34.82 ± 0.82 and 43.78 ± 0.9, standard lengths were 26.27 ± 0.64, 29.43 ± 0.73 and 37.35 ± 0.91 for (20-30cm, 30-40 cm and 40-50 cm), respectively. Numbers of rays on dorsal fin were 7.5 ± 0.18, 7.8 ± 0.25 and 8.08 ± 0.05; numbers of scales were 5, 5 and 5 ± 17 for (20-30cm, 30-40 cm and 40-50 cm) lengths, respectively. The values of WBC were (1345.1 ± 314.22, 15133564 ± 2851414 and 19536900 ± 4594589 /mm3), the values of RBC were recorded as 13885000 ± 2653096, 1317132.3 ± 91643.55 and 2077000 ± 139033/mm3 . The values of Hemoglobin (Hb) were 11 ± 0.95, 6.24±0.18 and 6.96 ± 0.25 g/dl. The values of PCV of were 45.4 ± 3.2, 25.6 ± 0.52 and 27.9 ± 0.97 % for (20-30cm, 30-40 cm and 40-50 cm) length, respectively. According to the results in the present study suggest that mersitic characters were affected by many environmental factors such as light, temperature and dissolved oxygen, while hematological parameters were affected by age. Res. Agric., Livest. Fish.6(1): 153-162, April 2019